Drafting of Online Meeting Minutes Based on Video Recording Using Topic Modelling - Rakhmat Arianto; Alwy Abdullah; Usman Nurhasan; Rokhimatul Wakhidah (SISFORMA, 2023)
Meeting minutes are important because they can track decisions and agreements made during the meeting. Meeting minutes can also be used as a benchmark for whether the meeting objectives have been achieved or not. Minutes are taken during the meeting until the end of the meeting, which contains essential points from the meeting. Minutes in online meetings are currently still done manually, and generally, every meeting is recorded as documentation that requires more Human Resources to change the recording of the meeting file Based on the problems above, a solution to this problem is needed by creating an automatic note-taking system that can assist the note-takers in concluding the meeting, especially in the Information Technology Department. This study uses the Latent Dirichlet Allocation (LDA) method to determine topic modeling. Based on this research, the system calculation using the LDA method produces the results obtained on the coherence score and similarity score only get an average value of 64.56% and 57.91% where these values are still less than optimal if used in actual conditions.